Boron fertilization and crop production in India: A review - SINGH, PRATIBHA; DWIVEDI, MANEESH; SRIVASTAVA, P C; PACHAURI, S P; SHUKLA, A K; SINGH, A P (The Indian Journal of Agricultural Sciences, 2020)
Boron (B) is an essential nutrient for normal growth of higher plants, and B availability in soil and irrigation water is an important factor of agricultural production. Boron deficiency is now becoming very common in many states of India. In the previous years, various studies have been conducted on boron, viz. factors affecting B availability to plants, its function in plant, B response in various crops, etc. The aim of the present review is to provide an update on recent findings related to these topics, which can contribute to a better understanding of B fertilization and the role of B in plants.